2023
DOI: 10.1101/2023.11.03.565492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphine-context associative memory and locomotor sensitization in mice are modulated by sex and context in a dose-dependent manner

Peter U. Hámor,
Matthew C. Hartmann,
Aaron Garcia
et al.

Abstract: Sex differences in opioid use, development of opioid used disorder, and relapse behaviors indicate potential variations in opioid effects between men and women. The locomotor and interoceptive effects of opioids play essential roles in opioid addiction, and uncovering the neural mechanisms underlying these effects remain crucial for developing effective treatments. In this study, we examined the dose-dependent effects of morphine on locomotor sensitization and the strength and stability of morphine-context ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Moreover, male animals display greater locomotor sensitization than females. However, other authors showed [ 62 ] opposing relationships between the locomotor effects of morphine and CPP in female vs. male adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, male animals display greater locomotor sensitization than females. However, other authors showed [ 62 ] opposing relationships between the locomotor effects of morphine and CPP in female vs. male adult mice.…”
Section: Discussionmentioning
confidence: 99%